Keterampilan Gerak Manipulatif Siswa Sekolah Dasar Berdasarkan Gender Pasca Pandemi Covid-19 - Betrisya Irwandi; Nuryadi Nuryadi; Agus Gumilar (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2023)
This study aimed to determine the basic manipulative movement skills of elementary school students based on gender after the Covid-19 pandemic. This research was conducted at the UPI Lab School Elementary School in Bandung. This study involved 144 students consisting of 78 male students and 66 female students. Data collection in this study was carried out by observing students' basic manipulative movement skills. The instrument used in this study uses the developed fundamental movement skill assessment format. The data analysis used is descriptive quantitative. The results showed that male students scored higher than female students, and there were differences in gender-based assessment categories between male and female students in mastering basic manipulative movement skills. Both are in a suitable category with a proportion of 56%. But they were based on the gender of male students in the excellent category, with a proportion of 55.4%, and female students in the moderate category, with a proportion of 72%. In conclusion, students' mastery of basic manipulative movement skills remains excellent after the Covid-19 pandemic. However, based on gender, male students are in a suitable category, and female students are in the excellent category. Keywords: Manipulative Movement, COVID-19 Pandemic, Physical Activity